2023
DOI: 10.1021/acschembio.3c00011
|View full text |Cite
|
Sign up to set email alerts
|

Unique Initiation and Termination Mechanisms Involved in the Biosynthesis of a Hybrid Polyketide-Nonribosomal Peptide Lyngbyapeptin B Produced by the Marine Cyanobacterium Moorena bouillonii

Abstract: Lyngbyapeptin B is a hybrid polyketide-nonribosomal peptide isolated from particular marine cyanobacteria. In this report, we carried out genome sequence analysis of a producer cyanobacterium Moorena bouillonii to understand the biosynthetic mechanisms that generate the unique structural features of lyngbyapeptin B, including the (E)-3-methoxy-2-butenoyl starter unit and the C-terminal thiazole moiety. We identified a putative lyngbyapeptin B biosynthetic (lynB) gene cluster comprising nine open reading frames… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 70 publications
2
7
0
Order By: Relevance
“…The kinetics for 1 under determined optimal conditions gave a K m = 70.2 ± 4.0 μM and k cat = 0.58 ± 0.01 s −1 (Figures S30 and S31), which suggests comparable overall catalytic efficiencies of DolJ and LynB7. 23 The diastereomeric analogue 2 was not active in the DolJ reaction (Figure 3A,B). We also prepared recombinant BarH (Figure S7), and it showed the same specificity toward compounds 1 and 2 as DolJ (Figure 3B).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…The kinetics for 1 under determined optimal conditions gave a K m = 70.2 ± 4.0 μM and k cat = 0.58 ± 0.01 s −1 (Figures S30 and S31), which suggests comparable overall catalytic efficiencies of DolJ and LynB7. 23 The diastereomeric analogue 2 was not active in the DolJ reaction (Figure 3A,B). We also prepared recombinant BarH (Figure S7), and it showed the same specificity toward compounds 1 and 2 as DolJ (Figure 3B).…”
mentioning
confidence: 98%
“…The product might then be oxidatively decarboxylated, potentially by DolJ, to result in Dol-10's final thiazole (Figure 2B). LynB7, which shares 78% identity to DolJ, was recently shown to mediate the same transformation in lyngbyapeptin B biosynthesis, 23 which may also occur in barbamide biosynthesis by BarH. 22 DolJ, BarH, and LynB7 are members of the nonheme diiron monooxygenase family (Figure S6), 23 which catalyzes a range of oxidation reactions (e.g., hydroxylation).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we demonstrated that AibH1H2 is a Mn/Fe-dependent monooxygenase that hydroxylates an aliphatic C–H bond of 2-aminoisobutyric acid . The protein components of AibH1H2 stem from a largely uncharacterized structural superfamily, PF04909, containing over 100,000 unique proteins that can individually function as either carboxylases, hydratases, hydrolases, or monooxygenases. Representatives of the latter enzyme classcollectively defined here as “amidohydrolase-related dinuclear oxygenases” (AROs)include PtmU3 and AibH2, , which employ dinuclear cofactors with different metal identities. In contrast, the other characterized PF04909 enzymes either lack a cofactor or employ a mononuclear metal site that can be Mn or Zn. , The primary structural features that differentiate mono- versus dinuclear active sites, engender monooxygenase functionality, and control the metalation of AibH2 and PtmU3 are unknown.…”
mentioning
confidence: 99%
“…Genome mining of the cyanobacterium Moorena bouillonii has revealed the enzymes involved in the biosynthesis of the hybrid PKS-nonribosomal peptide lyngbyapeptin B 24 . 22 This work allowed characterisation of the O -methyltransferase domain from the LynB2 PKS module, which generates the ( E )-3-methoxy-2-butenoyl starter unit that feeds nonribosomal peptide assembly. Various 2,3-diaminopropionates have been synthesised and investigated as alternative precursors during monobactam biosynthesis.…”
mentioning
confidence: 99%